Integration of Science Integrated Learning in Science E-Modules to Enhance Junior High School Students’ Computational Thinking Skills: A Literature Review - Herawadini, Fitria; Muslihatun, Fitri; Nabila, Elya Suci; Nurmayanti, Diyah (Indonesian Publication Center, 2026)
Science learning in the 21st century requires the development of computational thinking as a key component of higher-order thinking skills in problem solving. However, classroom practices remain predominantly teacher-centered and memorization-oriented, limiting students’ active involvement in analytical and systematic problem-solving activities. This study aims to analyze the integration of Science Integrated Learning in science e-modules and its contribution to enhancing junior high school students’ computational thinking skills. This study employed a literature review approach with a descriptive-narrative method by examining 36 relevant scientific articles published between 2021 and 2025. Data were collected through Google Scholar as the main database and supported by metadata checking through journal websites, DOI, SINTA, ERIC, ScienceDirect, and Scopus, using keywords related to Science Integrated Learning, science e-modules, and computational thinking. The results indicate that Science Integrated Learning functions as an integrative and contextual learning approach, while science e-modules serve as digital media that facilitate interactive, systematic, and independent learning. The integration is implemented through various strategies, including Problem-Based Learning, Project-Based Learning, STEM, inquiry, and engineering design processes, which support the development of decomposition, pattern recognition, abstraction, and algorithmic thinking. Furthermore, Android-based e-modules and digital flipbooks are practical and effective in increasing student engagement, conceptual understanding, scientific literacy, and problem-solving skills, indicating their strong potential to enhance the quality of science learning.